PERAN ELITE SUKU TENGGER DALAM PEMILU 2019 DI DESA ARGOSARI KECAMATAN SENDURO KABUPATEN LUMAJANG - Muhammad Kemal Mubarok; Priyatmoko Priyatmoko (Universitas Airlangga, 2021)
This research focuses on the roles of the elite in the Tengger Tribe in the last 2019 elections, more precisely discussing matters related to authority and authority in the successful holding of the 2019 elections yesterday. This elite which is divided into several segments is a channel for the aspirations of the lower classes. The minimal knowledge of the Tengger Tribe regarding politics and government makes some actions and choices tend to follow the local elites. In this case, the elite in the eyes of Max Weber, dividing it into three types according to social relations. The three types are traditional authority types which in Tengger society are occupied by adat pandhita shamans, charismatic authority types which are occupied by Hindu religious leaders and Islamic religious leaders, and the last is formal legal authority type occupied by the Argosari village head. Concerning the 2019 General Elections, each has its own mass base in terms of the type of authority. Even though the village head, traditional shaman, Muslim and Hindu community leaders, do differ in their political choices, they still uphold democratic values along with their traditional values. Some philosophies related to democracy and elections according to the elite and the Tengger community are the same as the life guidelines handed down from their ancestors. Tengger Tribe living guidelines include, among others, Tenggering benevolence, Sesanti Titi Luhur, Disathru, and Hila-Hila which are instructions for democracy. The implementation of elections and democracy in peace will be realized when the Tengger Tribe people follow the guidelines of their ancestors. Thus, the motto adopted by the local community can be realized